(3LGeY GdeHGOF hGdZGjGJ aj Yde GdejbGJs - (3CHh Ydj TQa GdOjf GdMSf Hf Ydj Hf YeQ GdeQGcTj,J (B660 (3g` s
(3ChdgG (B:s
(3GYde habc Gddg Gfi QCjJ ai JSgjd eG bOeJ PcQg hMaXg (B( (3Cfi QCjJ (B) (3Gdege ef GdMSGHGJ ai LOhd hGMO s
(3BNQgG (B:s
(3LjH YQV GdHdO , Xd JeGe SYI GdeTQb GdeYchS SJhf GdXd GdeYchS dfUa bhS GdSeGA s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3fSNI KGfjI (B_ (3LRA efg GdaUd GdSGHY hGdKeGfhf hgh GdCNjQ ef Gdaf GdChds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B203 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B286s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B625 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B866 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B572s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B125) s
Keywords: (3Gdadcs